1996
DOI: 10.1128/jb.178.11.3293-3307.1996
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi supercoiled plasmids encode multicopy tandem open reading frames and a lipoprotein gene family

Abstract: DNA sequencing and Southern blot analyses of a Borrelia burgdorferi DNA fragment encoding a signal sequence led to the discovery of a genetic locus, designated 2.9, which appears to be present in at least seven copies in virulent B. burgdorferi 297. DNA sequence analysis of these regions revealed that each 2.9 locus contained an operon of four genes (ABCD) and open reading frames designated rep ؉ (positive strand) and rep ؊ (negative strand) which encoded multiple repeat motifs. Downstream of the rep ؉ gene(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(173 citation statements)
references
References 52 publications
8
164
1
Order By: Relevance
“…2), which contained three open reading frames (ORFs) termed orfX, blyA, and blyB. blyA and blyB correspond to orfA and orfB, respectively, of the ABCD operon described recently by Porcella et al (1996), while orfX is separated from this operon by a 156 bp intergenic region. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2), which contained three open reading frames (ORFs) termed orfX, blyA, and blyB. blyA and blyB correspond to orfA and orfB, respectively, of the ABCD operon described recently by Porcella et al (1996), while orfX is separated from this operon by a 156 bp intergenic region. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA fragments were generated using purified plasmid encoding the strain 297 2.9-7lpA and 2.9-7lpB genes (33) as template and the following forward and reverse primers: 5 Ј -GGGGATCCTGCGCTGCTAAT-GATACACAG-3 Ј (BamHI site plus nucleotides 2205-2225) and 5 Ј -GGGAATTCCCTTTTTCTTATGACTAATTATTGC-3 Ј (EcoRI site plus nucleotides complementary to bases 2596-2572) for 2.9-7lpA and 5 Ј -GGGGATCCTGCAATGCTAATGATAATGATAC-3 Ј (BamHI site plus nucleotides 2655-2677) and 5 Ј -GGGAATTCGAGAAA-TGTTTTTAGTTTTGCC-3 Ј (EcoRI site plus nucleotides complementary to bases 3244-3223) for 2.9-7lpB. Construction of the recombinant 2.9-4Lp-GST fusion protein has been described previously (33). The resulting GST fusions were purified by affinity chromatography on an agarose-glutathione matrix according to manufacturer's instructions (Pharmacia LKB Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…The other, a 203-bp product amplified from DMC-grown spirochetes, was part of an open reading frame encoding a homologue for MutS, a methyl-directed DNA mismatch repair enzyme (49) which corresponds to gene Bb098 from the B. burgdorferi strain B31 chromosome (48). The sequence of the 11th product, also specific to DMC-grown organisms, was an exact match for a gene encoding a borrelial lipoprotein (2.9-7LpB) which belongs to a family of differentially expressed genes located on homologous 32-and 18-kb circular plasmids (33,50). 2.9-7lpB lies immediately downstream of a related gene which encodes another lipoprotein (2.9-7LpA); sequence analysis suggested that 2.9-7lpA and 2.9-7lpB are transcriptionally linked (33).…”
Section: B Burgdorferi 297 Replicates and Alters Its Antigenic Compomentioning
confidence: 99%
“…The megabase-sized chromosome and a variable array of plasmids constitute the linear DNA molecules (Barbour and Garon, 1987;Barbour, 1988;Baril et al, 1989;Ferdows and Barbour, 1989;Davidson et al, 1992;Casjens and Huang, 1993;Casjens et al, 1995). The circular component of the genome consists of a circular plasmid of 26-28 kb (called cp26; Schwan et al, 1988;Simpson et al, 1990;Hinnebusch and Barbour, 1992;Marconi et al, 1993;Sadziene et al, 1993) and a family of related 32 kb plasmids (Porcella et al, 1996;Stevenson et al, 1996;Zü ckert and Meyer, 1996;Casjens et al, 1997), in addition to a variable collection of others (Barbour, 1988;Hyde and Johnson, 1988;Simpson et al, 1990;Dunn et al, 1994;Xu and Johnson, 1995). Although a strain without linear plasmids has been isolated (Sadziene et al, 1993), loss of cp26 has never been observed, suggesting that the plasmid has unique importance for the B. burgdorferi life cycle.…”
Section: Introductionmentioning
confidence: 99%